2021
DOI: 10.1002/tsm2.257
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of countermovement jump force profiles in youth athletes

Abstract: The purposes of this study were to determine whether countermovement jump (CMJ) force profiles differ for jumps in which peak force occurred at the low position of the countermovement (LP) compared to jumps in which peak force did not occur at the low position of the countermovement (NLP), and compare relationships among CMJ and isokinetic metrics between groups. Thirty‐nine male and female youth athletes between 9‐ and 17‐year‐old participated. Participants completed CMJs and isokinetic knee extensions from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…In contrast, isokinetic muscle strength testing provides information on a range of muscle properties. 8 The model can evaluate the properties of muscles under concentric and eccentric contractions.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, isokinetic muscle strength testing provides information on a range of muscle properties. 8 The model can evaluate the properties of muscles under concentric and eccentric contractions.…”
Section: Resultsmentioning
confidence: 99%
“…Another unique method by which CMJs and SLJs may be assessed is by examining the efficiency of the force-time signal (12,26), which involves examining the peak force of the force-time signal relative to the low position of the countermovement. In Division I NCAA athletes, McHugh et al (26) suggested that peak force occurring at the bottom of the countermovement may yield superior eccentric (unweighting and braking phase) and performance metrics than when peak force does not occur at the bottom of the countermovement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (12,26) have stated that if the force at the low position of the countermovement is within 1% of the peak force, then the jump is considered more biomechanically efficient. Therefore, an efficiency index was calculated for each jump using the following equation (12,26): (peak force − force at the low position)/peak force. This metric was used to determine the efficiency of the vertical jumps (i.e., closer to 0.01 [1%]) before and after the strength and conditioning program.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations